2022
DOI: 10.1136/ijgc-2022-003543
|View full text |Cite
|
Sign up to set email alerts
|

Management of oligometastatic ovarian cancer recurrence during PARP inhibitor maintenance

Abstract: ObjectiveThe benefit of surgery and maintenance treatment with PARP inhibitors (PARPi) has been clearly demonstrated in ovarian cancer. Also, the efficacy and safety of stereotactic body radiotherapy has been shown in patients with metastatic, persistent, and recurrent disease. The aim of this study is to evaluate the management of oligometastatic progression during PARPi maintenance treatment.MethodsThis is an observational, retrospective, single-arm study conducted from June 2017 to December 2020 in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
(51 reference statements)
0
11
0
1
Order By: Relevance
“…To note that currently there is no consensus about the PARP-I reduction or the optimal time to suspend PARP-I before and after RT in MPR ovarian cancers. In our clinical practice, PARP-I were stopped before the treatment and, similarly to the SBRT published data, [25] this approach seemed not to increase toxicity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To note that currently there is no consensus about the PARP-I reduction or the optimal time to suspend PARP-I before and after RT in MPR ovarian cancers. In our clinical practice, PARP-I were stopped before the treatment and, similarly to the SBRT published data, [25] this approach seemed not to increase toxicity.…”
Section: Discussionmentioning
confidence: 79%
“…In oligometastatic settings, the achievement of high ORR has proved to be a pivotal goal of any locoregional treatment, including RT [24] , allowing in the case of ovarian cancer to raise a “drug-free holiday”, crucial in the chronicization of the disease. In this “ PARP-I era ”, all efforts should be made to avoid a rechallenge with cytotoxic platinum-based chemotherapy, considering that platinum-sensitive MPR ovarian cancers are eligible for PARP-I [25] . This issue is crucial, knowing that, in the OReO/ENGOT Ov-38 trial the maintenance with olaparib rechallenge was effective in overall progression-free survival regardless of BRCA status [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies suggested that patients with oligometastatic progression under PARPi may continue to benefit from PARPi maintenance if managed with locoregional treatment, either surgery or stereotactic body radiotherapy 4849 The rationale behind this is that locoregional treatment may remove those neoplastic clones that developed PARPi resistance while the rest of the disease remains stable under PARPi influence.…”
Section: Is There a Place For Parpi Rechallenge?mentioning
confidence: 99%
“…The incidence of OMD varies depending on the type of tumors. It was hypothesized in the past that some cancers such as pancreatic adenocarcinoma and small-cell lung cancer, never present with an oligo-metastatic behavior; to date, an oligo-metastatic status has been reported in all cancers [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The incidence of OMD varies greatly among cancer types, ranging from extremely rape (such as SCLC where only a few case reports are described) [ 21 ] to 10–40% of HCC [ 25 , 26 ].…”
Section: Epidemiology Of Omdmentioning
confidence: 99%